The mechanics of formation of heat-induced myofibrillar protein gel from rabbit psoas major - Luqi Wei; Baowei Cui; Muneer Ahmed Jamali; Teng Hui; Shixin Liu; Yingjie Bao; Zengqi Peng; Yawei Zhang (CyTA - Journal of Food, 2017)
The present study was designed to analyze the formation mechanics of heat-induced myofibrillar gels from rabbit psoas major at 0.6 mol/L KCl (pH 6.5) and 0.2 mol/L KCl (pH 6.0; n = 3). Morphological structure changes were observed using phase-contrast microscopy, transmission electron microscopy, scanning electron microscopy (SEM) and gel properties were determined through water-holding capacity (WHC), gel strength and dynamic rheological test. The results revealed that myofibrillar filaments aggregated and formed larger oligomers by side-by-side interactions when heated from 25 to 65°C. In higher ionic strength at higher pH, the filaments formed a more compact homogeneous network structure and the G′ value was much lower with higher WHC and gel strength, suggesting that the myofibril gel properties could be described by ∆G′. Based on the present study, it is suggested that the desired structural and textural attributes of myofibril gel can be manipulated by temperature, ionic strength and pH.